Ações de Atenção Básica à Saúde da mulher em penitenciárias na Paraíba - Mesquita, Vanessa Giulianni de Freitas (2016)
Objective: to describe the prenatal, cervical cancer and breast cancer control actions performed in women's penitentiaries in Paraíba and to identify positive and negative aspects for the execution of women's healthcare actions in Paraíba penitentiaries under the perspective of women deprived of liberty, health professionals and managers. Methodological path: a descriptive-exploratory study of a qualitative approach, performed between June and November 2015, in the four female penitentiaries of Paraíba. Participants included women deprived of liberty, nurse from a health unit implanted in a state prison unit, and nurses who performed weekly care in other prisons, SEAP Health Management and women health coordinators of the Municipal Health Secretariats. For data collection, an interview with semi - structured script was used. All the professionals were interviewed and the sample of women deprived of liberty was given by theoretical saturation in each prison unit. The participant´s speeches of the research were associated through the triangulation technique and the data analysis followed the methodological proposal of Content Analysis, according to Bardin's perspective. Results: it was possible to understand which actions of basic care regarding prenatal care, cervical cancer control and breast cancer control were developed, as well as the educational actions performed. In addition, the positive aspects of basic healthcare actions for women deprived of liberty and the obstacles to the implementation of these actions were identified. Conclusions: the actions of cervical cancer control and prenatal care stand out in the control of breast cancer; educational actions do not achieve the expected results for health promotion; the existence of actions of basic attention to women's health is positively evaluated regarding aspects of healthcare, which was not observed with regard to health promotion actions; it was found that poor physical structure, lack of inputs for healthcare, spontaneous demand, lack of professionals and political differences are considered obstacles and factors that make integral healthcare of these women unfeasible.